DOI: 10.14264/uql.2016.62
|View full text |Cite
|
Sign up to set email alerts
|

Low optical gap materials for organic solar cells - research and application

Abstract: In spite of the cost of silicon solar cells decreasing in recent years, there is considerable interest in solar cells with lightweight and flexible forms. Organic semiconductor-based photovoltaic cells (OPVs) have the potential to offer low cost, lightweight and flexible devices. At this stage there is still much to be improved for OPVs as the efficiencies are still lower than their inorganic counterparts. Polymeric materials have been more widely studied than their non-polymeric counterparts. In recent years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 91 publications
1
1
0
Order By: Relevance
“…The organic phase was then dried over anhydrous sodium sulphate and solvents removed to give 2.14 as a pale yellow solid (3.16 g, 39%). The 1 H NMR and TLC retention time were consistent with an authentic sample 278.…”
supporting
confidence: 69%
See 1 more Smart Citation
“…The organic phase was then dried over anhydrous sodium sulphate and solvents removed to give 2.14 as a pale yellow solid (3.16 g, 39%). The 1 H NMR and TLC retention time were consistent with an authentic sample 278.…”
supporting
confidence: 69%
“…As discussed within the retrosynthetic analysis, previous work has found that the aldehyde derivative, 2.14, is not suitable for direct C-H activated arylations due to functional group interference leading to low yields and unwanted by-products. 278,282,283 Therefore, the aldehyde functional group was protected with ethylene glycol in a refluxing solution containing p-toluene sulfonic acid and toluene fitted with a dean stark condenser. The acetal derivative was isolated in a 91 % yield.…”
Section: Synthesis and Preparationmentioning
confidence: 99%